Parishes Registers and Lists of Parishes Residents in the Wróblewski Library of the Lithuanian Academy of Sciences: Genesis and Confessional Singularity - Žilys, Saulius (Bibliotheca Lituana, 2012)
The article treats baptismal, matrimonial and death parish registers in 17th–20th centuries, also lists of confirmees and lists of converts to Roman Catholic Church or Orthodox Church, lists of parishes and parishes’ residents of territories in Lithuania, Belarus, Poland and East Prussia. Manuscript materials used in article belong to various Christian and non-Christian confessions: Roman Catholic, orthodox, uniate, evangelical reformers, evangelical Lutheran, Karaite, Jew/Hebrew, Tartar. The article treats origin of parishes’ registers chronology, how parishes’ registers were written, and which information was in them also defines confessional singularity. Focus on 17th–18th century parishes registers – mostly Roman Catholic. Church parishes registers at first were started to write in Italy (1396) and in Provence. The Council of Trent of Roman Catholic Church in 1563 obligated fill in baptismal and matrimonial parish registers, ordinary “Rituale romanorum” in 1614 obligated to fill in death registers and lists of parishes residents. Filling of parishes registers in Roman Catholic and Protestant churches became overall in 17th century, in Orthodox and Uniate churches – in 18th century. The first information about parishes’ registers in Lithuania was introduced in visiting-round of Samogitia bishop in 1579, but the oldest known parish register is baptismal register of Joniškis church and it begins in 1599. The article treats evolution of parishes’ registers in Lithuania. Noticeable that death registers were started to fill only in 17th century and involved only part of departed.